Circulating Sclerostin Levels Are Positively Related to Coronary Artery Disease Severity and Related Risk Factors. (9th December 2021) - Frysz, Monika; Gergei, Ingrid; Scharnagl, Hubert; Smith, George Davey; Zheng, Jie; Lawlor, Deborah A; Herrmann, Markus; Maerz, Winfried; Tobias, Jon H
ABSTRACT: Romosozumab is a newly available treatment for osteoporosis acting by sclerostin inhibition. Its cardiovascular safety has been questioned after finding excess cardiovascular disease (CVD)‐related events in a pivotal phase 3 trial. Previous studies of relationships between circulating sclerostin levels and CVD and associated risk factors have yielded conflicting findings, likely reflecting small numbers and selected patient groups. We aimed to characterize relationships between sclerostin and CVD and related risk factors in more detail by examining these in two large cohorts, Ludwigshafen Risk and Cardiovascular Health study (LURIC; 34% female, mean age 63.0 years) and Avon Longitudinal Study of Parents and Children study (ALSPAC) mothers (mean age 48.1 years). Together these provided 5069 participants with complete data. Relationships between sclerostin and CVD risk factors were meta‐analyzed, adjusted for age, sex (LURIC), body mass index, smoking, social deprivation, and ethnicity (ALSPAC). Higher sclerostin levels were associated with higher risk of diabetes mellitus (DM) (odds ratio [OR] = 1.25; 95% confidence interval [CI] 1.12, 1.37), risk of elevated fasting glucose (OR 1.15; CI 1.04, 1.26), and triglyceride levels (β 0.03; CI 0.00, 0.06). Conversely, higher sclerostin was associated with lower estimated glomerular filtration rate (eGFR) (β −0.20; CI −0.38, −0.02), HDL cholesterol (β −0.05; CI −0.10, −0.01), and apolipoprotein A‐I (β −0.05; CI −0.08, −0.02) (difference in mean SD per SD increase in sclerostin, with 95% CI). In LURIC, higher sclerostin was associated with an increased risk of death from cardiac disease during follow‐up (hazard ratio [HR] = 1.13; 1.03, 1.23) and with severity of coronary artery disease on angiogram as reflected by Friesinger score (0.05; 0.01, 0.09). Associations with cardiac mortality and coronary artery severity were partially attenuated after adjustment for risk factors potentially related to sclerostin, namely LDL and HDL cholesterol, log triglycerides, DM, hypertension, eGFR, and apolipoprotein A‐I. Contrary to trial evidence suggesting sclerostin inhibition leads to an increased risk of CVD, sclerostin levels appear to be positively associated with coronary artery disease severity and mortality, partly explained by a relationship between higher sclerostin levels and major CVD risk factors. © 2021 The Authors. Journal of Bone and Mineral Research published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research (ASBMR).